Preparation and characterization of cefixime-loaded liposomes"" (Latakia University Journal -Medical Sciences Series, 2024)
This research aimed to prepare liposomes containing cefixime. The phospholipids forming liposomes envelopes were extracted locally from egg yolk. Cefixime was chosen as an active drug because of its anti-cancer properties, by inhibiting the biosynthesis of nucleic acids and proteins in cancer cells and by its binding to cellular DNA.Liposomes were prepared by Bingham method (hydration of thin film) and they were homogeneous and almost spheric. The prepared liposomes were investigated for structure, particle size and encapsulation efficiency (EE). Different factores were studied (eg: cefixime and cholesterol quantites).The dimensions ranged between 1and 50 microns and the EE(s) were between 94 and 98%. An increase in the particles size and EE was observed by increasing cholesterol and cefixime quantities (p < 0.05). However when the amount of cefixime was reduced, the EE was reduced (p > 0.05).